Levels of generalized anxiety, moral distress, and moral courage among nurses: A comparative study in COVID-19 and non-COVID-19 wards - Seyede Fatemeh Gheiasi; Ahmad Reza Abedi; Mahboobeh Khosravani; Fatemeh Rafiei; Andrew Fournier; Maryam Ebrahimabadi (Preventive Care in Nursing and Midwifery Journal)
Background: During the COVID-19 pandemic, nurses faced high levels of anxiety and moral distress. Nurses need moral courage to uphold proper moral performance. Objectives: This study aimed to compare the levels of anxiety, moral distress, and moral courage of nurses working in COVID-19 and non-COVID-19 wards. Methods: This descriptive comparative study was conducted on 107 nurses working in COVID-19 (n=53) and non-COVID-19 (n=54) wards at Zanjan University of Medical Sciences. Participants were selected using a convenience method. Data were collected using the Generalized Anxiety Disorder (GAD), Moral Distress Scale (MDS), and Professional Moral Courage (PMC) questionnaires. Data analysis was performed using descriptive and inferential statistics in SPSS 16 software. Results: The majority of participants in the study were female (66%) and married (54.7%). There was no statistically significant difference in the mean (SD) generalized anxiety score between nurses in COVID-19 and non-COVID-19 wards [5.51 (2.53) vs. 4.83 (2.50), p=0.168]. The comparison of the mean (SD) moral distress score in nurses in COVID-19 and non-COVID-19 wards did not show a statistically significant difference [1.48 (0.71) vs. 1.70 (0.58), p=0.078]. Similarly, no significant difference was found in the mean (SD) score of moral courage between the two groups caring for COVID-19 and non-COVID-19 patients [59.66 (8.28) vs. 60.46 (6.06), p=0.983]. Conclusion: The study reveals elevated generalized anxiety in COVID-19 ward nurses compared to non-COVID-19 counterparts. No significant differences in moral distress severity or moral courage highlight shared resilience and commitment, emphasizing tailored support for nurses in varied environments.